Sugar consumption pattern among cardiometabolic risk individuals: a scoping review - Chiang, Wan Ling; Azlan, Azrina; Mohd Yusof, Barakatun Nisak (Bentham Science Publishers, 2022)
Background: The global prevalence of noncommunicable diseases has risen rapidly over the past decade. Research has focused on dietary management, particularly dietary sugar, to prevent and treat noncommunicable diseases. Objective: This study undertakes a scoping review of research on the impacts of dietary sugar on cardiometabolic related health outcomes. Methods: Ovid Medline, Scopus and Web of Science Core collection databases were used to identify papers published from January 1, 2010 onwards. The included studies had to be cross-sectional or cohort studies, peered review, published in English and in adults, aged 18 years old and above. Articles had to determine the impacts of sugar intake on cardiometabolic related health outcomes. Study quality was measured using the Quality Assessment Tool for Observational Cohort and Cross-sectional Studies. In addition, a narrative synthesis of extracted information was conducted. Results: Thirty-one articles were included in this review. All studies had a large sample size, and the exposure measure was clearly defined, valid and applied consistently across all study participants. Exposure was measured using validated questionnaires. All data were statistically analysed and adjusted for critical potential confounding variables. Results showed that dietary sugar intake was significantly associated with metabolic syndrome, blood pressure, blood glucose, blood lipids, and body weight. Conclusion: Dietary sugar intake significantly increased cardiometabolic risks through mechanisms dependent and independent of weight gain. It is essential to create public awareness on the topics of cardiometabolic risk management and dietary sugars intake.